Inflammation and Regeneration - Okano, Hideyuki; Mimori, Tsuneyo
Inflammation and Regeneration is the official international journal of the Japanese Society of Inflammation and Regeneration (JSIR). This journal provides an open access forum which covers a wide range of scientific topics in the research field of basic and clinical regenerative medicine. Inflammation research and regenerative medicine are tightly linked research areas in life sciences and their significance in translational research is rapidly increasing. From this aspect, this journal encourages the submission of manuscripts whose scope bridges these fields of research. Inflammation and Regeneration publishes papers in the following categories: research article, note, rapid communication, case report, review and clinical drug evaluation.